‘IMAGE‘ KOTA GOETTINGEN DAN SEKITARNYA SEBAGAI SALAH SATU TUJUAN WISATA ALAM DAN REKREASI LUAR RUANGAN (STUDY KASUS MENURUT MAHASISWA INTERNASIONAL DI UNIVERSITAS GOETTINGEN) - Lambok P. Sagala; Renate Bürger-Arndt; Christoph Dittrich (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2016)
Nature tourism/outdoor recreation is one the fastest growing tourism activities in the world. More and more people travel to natural sites due to increased environmental awareness and a high degree of urbanization.The objective of this research was to capture the image of Göttingen and its surrounding area, using a combination of structured and unstructured methods as recommended by previous researchers. The image determination was considered important for positioning and differentiating the destination from other competitors. From a marketing point of view, image determination could increase tourist interest to visit the destination, travel satisfaction, and intention to return. The structured method used image attributes, which were evaluated using a 5-point Likert scale while the unstructured method used three open-ended questions. In addition, the research was also done to identify the nature of outdoor recreation/nature tourism among international students. The study focused on international students, which have certain characteristics that are different from those of domestic students. Data was taken from January to April 2014. 326 respondents delivered useable responses/data. This research revealed that a combination of structured and unstructured methods was able to capture the underlying image dimension of Göttingenand its surroundings. Considering the high propensity for travelling and previous travel experience of the students, it could be interpreted that international students at Göttingen University are one of the prospective nature tourism markets. Therefore, customized marketing strategy could be applied to attract them.